Lizard Wears Shades. A Spectacled Sphenomorphus (Squamata: Scincidae), from the Sacred Forests of Mawphlang, Meghalaya, North-east India - Aniruddha, Datta Roy; Das, I.; Bauer, Aaron M.; Lyngdoh Tron, Ronald K.; Karanth, Praveen (Zootaxa, 2013)
A new species of lygosomatine scincid lizard is described from the sacred forest of Mawphlang, in Meghalaya, north-eastern India.